Static Electronic ETLE Electronic Tickets In Traffic Violations Processing At The Bengkulu Regional Police Traffic Directorate - Aprilawa Grasella AS; Alauddin, Alauddin; Rosmanila, Rosmanila (SEAN Institute, 2025)
The ETLE system, which was launched in Bengkulu City on March 26, 2022, aims to address the increasing traffic violations and limitations of manual enforcement. With the installation of cameras at strategic points across the city, the system records and stores traffic violations as evidence for legal processes. This study explores the implementation of the ETLE system in Bengkulu, focusing on its effectiveness in traffic law enforcement, the challenges faced, and its impact on driver behavior. The research employs an empirical legal (socio-legal) approach, using both primary data (field research) and secondary data (library research). The fieldwork includes interviews with police officers from the Bengkulu Police Traffic Directorate (Ditlantas) and violators of the ETLE system. Data collection methods include interviews and library research, with qualitative data analysis presented through narrative form. The study finds that the ETLE system has significantly improved the efficiency of traffic law enforcement in Bengkulu, as it automates the detection and processing of violations. The use of cameras equipped with Artificial Intelligence allows for the accurate identification of violations such as seatbelt non-use, speeding, and mobile phone use while driving. The system also offers greater transparency and fairness in law enforcement, as violators can easily check their violations and pay fines electronically. Despite its successes, the study highlights challenges, including issues with internet connectivity, power outages, and outdated vehicle registration data, which can hinder the system's effectiveness. Nonetheless, the implementation of ETLE has contributed to raising public awareness about traffic regulations and has encouraged more disciplined driving behavior in Bengkulu. The findings suggest that this system can be an effective model for other regions in Indonesia aiming to enhance road safety and traffic law enforcement.